RANCANG BANGUN APLIKASI REKOMENDASI PEMBELIAN LAPTOP DENGAN METODE FUZZY DATABASE MODEL TAHANI BERBASIS WEB - Hendry Setiawan; Seng Hansun (Komputa : Jurnal Ilmiah Komputer dan Informatika, 2014)
A laptop is a computer that looks compact, small, lightweight and easy to carry anywhere. But choosing a laptop is not an easy thing for consumers who want to have a laptop as per the specifications and budget of the consumer finance. Therefore the purpose of this research is to build a web-based application that can give recommendation to purchasers or consumers as needed. The application is built by using PHP programming language and implementing the Fuzzy Database Tahani model which is still using the standard relation of fuzzy logic, and also using MySQL database for the data storage. It is found that the Fuzzy Database Tahani model can be implemented on the application built on to give a correct recommendation for the consumers.